PELATIHAN DESAIN DAN INOVASI PACKAGING UNTUK MENINGKATKAN DAYA TARIK PRODUK IBU IBU PKH - Yulis Mawati; Budiyono; Rohiman; Muhammad Gandung (Abdi Jurnal Publikasi, 2026)
Packaging design and innovation are important factors in increasing product attractiveness, especially for micro-enterprises managed by Family Hope Program (PKH) women. In practice, many products produced by PKH women still use simple packaging without attractive visual design, proper labeling, or clear product identity. This condition results in low consumer interest and weak product competitiveness in the market.This community service activity aims to improve the knowledge, skills, and creativity of PKH women in designing and innovating product packaging in order to add value and enhance product appeal. The methods used in this program include socialization, training, hands-on practice, and evaluation. The training materials cover packaging functions, basic packaging design principles, selection of appropriate packaging materials, label creation, and simple branding implementation.The results show an improvement in participants’ understanding and ability to produce more attractive, neat, informative, and hygienic product packaging compared to before the training. Products developed after the training have clearer identities and more professional appearances. This activity demonstrates that packaging design and innovation training can enhance product attractiveness and potentially support increased competitiveness and economic empowerment of PKH women.